Bangladesh Seed Systems Product Diary - Habib, Muhammad Ashraful; Nayak, Swati; Islam, Saidul (Rice Today, International Rice Research Institute, 2025)
Rice is the primary staple food in South Asia and a vital source of livelihood for millions of farming households. In response to climate change and evolving market demands, Bangladesh’s leading research institutions—BRRI and BINA—have developed improved rice varieties with higher productivity and greater resilience. This Seed Systems Product Diary presents selected new rice varieties evaluated through farmer-managed on-farm and adaptive trials conducted by IRRI and national partners across diverse agro-ecological zones of Bangladesh. These trials reflect real field conditions, including drought-, salinity-, and flood-prone environments. Each entry provides a concise profile of a high-performing rice product suited to specific ecosystems or market segments. The diary serves as a practical decision-support tool for seed producers, extension agents, agri-entrepreneurs, and institutional stakeholders, facilitating evidence-based varietal selection, seed multiplication, and scaling to enhance farm productivity, income, and food security.